Pythor's revenge - Rusu, Meredith (LEGO Ninjago., 2017)
" ... When Pythor hears about the BorgWatch--a top secret new invention from Dr. Cyrus Bord--he sees an opportunity to best the ninja in a new and different way. He swipes part of the BorgWatch from under their noses and threatens to reveal it on TV. Catching Pythor should be a simple task for six Master Spinjitzu, right? But Pythor is as slippery as a, er snake. Can the ninja stop their longtime enemy before he slithers his way into the spotlight?"--Back cover.